Scour Characteristics and Equilibrium Scour Depth Prediction around a Submarine Piggyback Pipeline - Ruigeng Hu; Xiuhai Wang; Hongjun Liu; Hao Leng; Yao Lu (Journal of Marine Science and Engineering, 2022)
Local scour around a submarine piggyback pipeline in combined waves and current is investigated experimentally. Based on the experimental results, the scour evolution and scour morphology are firstly analyzed. Then, a comparison with the equilibrium scour depth Seq between the present experimental data and predicted results is conducted. After that, the correlation between the dimensionless scour timescale T* and the maximum Shields parameter θcw is investigated, and a formula is obtained to describe the variation trend between T* and θcw for different gap ratios G/D. Furthermore, the parametric study is carried out to study the effects of Reynolds number Red and θcw on Seq, respectively. The results indicate that the Seq below the piggyback pipeline increases when the gap ratio G/D increases from 0 to 0.1, and it gradually decreases when G/D > 0.1. For a given KC, the Seq increases with the increase of the ratio of velocities Ucw. In addition, when Ucw is fixed, a higher KC results in a greater Seq. The T* is closely related to θcw and G/D. The higher Red and θcw both tend to result in the greater scour depth below a piggyback pipeline in combined waves and current.